Landing from different heights: Biomechanical and neuromuscular strategies in trained gymnasts and untrained prepubescent girls - Christoforidou, A.; Patikas, D. A.; Bassa, E.; Paraschos, I.; Lazaridis, S.; Christoforidis, C.; Kotzamanidis, C. (Journal of Electromyography and Kinesiology, 2017)
The purpose of this study was to examine the biomechanics of the lower limb, during landing in female prepubertal gymnasts and prepubertal untrained girls, aged 9-12 years. Ten healthy participants were included in each group and performed five landings from 20, 40, and 60 cm. Kinematics, ground reaction forces (GRF) and electromyogram (EMG) from the lateral gastrocnemius, tibialis anterior, and vastus lateralis are presented. Gymnasts had higher vertical GRF and shorter braking phase during landing. Compared to untrained girls, gymnasts exhibited for all examined drop heights more knee flexion before and at ground contact, but less knee flexion at maximum knee flexion position. Especially when increasing drop heights the gymnasts activated their examined muscles earlier, and generally they had higher pre- and post landing EMG amplitudes normalized to the peak EMG at 60 cm drop height. Furthermore, gymnasts had lower antagonist EMG for the tibialis anterior compared to untrained girls, especially when landing from higher heights. It is concluded that the landing strategy preferred by gymnasts is influenced by long-term and specialized training and induces a stiffer landing pattern. This could have implications in injury prevention, which requires further investigation.